Design of Fatigue Life Test System of the Energy Efficient Heavy Transmission - Tan Wei; Xu Ran; Mi Lin; Chen Sheng (Jixie chuandong)
During the development process of heavy transmission,a cyclic loading fatigue life test is required to carry out in a certain load to verify the reliability of the internal gear,shaft,bearing,box,and the overall system. In order to adapt the needs of high power and big torque fatigue life test of heavy transmission,an electric-closed fatigue life test system based on energy recovery technology of common DC bus is designed.The test system takes industrial control computer and PLC as the centralized control core unit and uses the SIEMENS S120 multi drive variable frequency speed control system to carry on the drive and load to the test transmission. The advanced technologies is integrated into the testing and control system,such as test process management,test automatic process control,multi thread signal monitoring,testing process data automatic storage,etc. The automation level and reliability of the testing work is improved. The test results show that the fatigue life test system is stable,reliable,convenient operation and at high control precision.